(untitled) (Biological Sciences - PJSIR, 2005)
The present paper attempts to investigate the effect of elastane concentration and knitting processing variables, such as tightness factor and take-down tension upon spirality and density of rib and single jersey fabrics. Five different concentrations of elastane (0-7%), three different take-down tensions (2, 3 and 5 kg) and four levels of tightness factors (12, 13.5, 15, and 16.5) were selected. Fabric density has a direct relationship with the concentration of elastane and tightness factors. Weight of both types of knitted fabrics increased with the increase in the tightness factor and the percentage of elastane. It was also found that with the increase in take-down tension and reduction in the tightness factor, the spirality increased.